Salts and cocrystal of etodolac: advantage of solubility, dissolution, and permeability - Rai, Sunil K.; Allu, Suryanarayana; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
{Etodolac (ETD) is a nonsteroidal anti-inflammatory drug (NSAID) approved by the United States Food and Drug Administration (US-FDA) in 1991 for the treatment of rheumatoid arthritis. Because of its poor aqueous solubility and high permeability, ETD falls under Biopharmaceutics Classification System (BCS) Class II drug. The present study was aimed to screen stable salts and cocrystals of ETD using Generally Recognized as Safe (GRAS) and a few non-GRAS coformers. Crystallization of five salts (i.e.